Viral Burden and Clearance in Asymptomatic COVID-19 Patients. (16th March 2022) - Gunatilaka, Avanka B; Marco, Nicholas; Read, Graham H; Sweeney, Maggie; Regan, Greg; Tsang, Cynthia; Abdulrahman, Lobna; Ampabathina, Swetha; Spindler, Archie; Lu, Sarah S; Schink, Elena; Gatti, Richard; et al.
Abstract: Background: Containing coronavirus disease 2019 (COVID-19) has been difficult, due to both the large number of asymptomatic infected individuals and the long duration of infection. Managing these challenges requires understanding of the differences between asymptomatic vs symptomatic patients and those with a longer duration of infectivity. Methods: Individuals from Los Angeles were tested for COVID-19, and a group positive for COVID-19 chose to have follow-up testing. Associations between symptoms and demographic factors, viral burden measured by cycle threshold (CT) value, and duration of polymerase chain reaction (PCR) positivity were analyzed. Results: Eighteen point eight percent of patients were positive for COVID-19. Asymptomatic COVID-19-positive patients were significantly younger than symptomatic patients (2.6 years; P  < .001). There were no differences in average CT between asymptomatic and symptomatic patients. The estimated median duration of COVID-19 PCR positivity was 23 days. Being asymptomatic throughout the course of infection was the only factor associated with a shorter course of COVID-19 PCR positivity (21 vs 28 days; P  = .002). Conclusions: We found important differences and similarities between asymptomatic and symptomatic COVID-19-positive patients, the most meaningful being a similar level of virus as measured by PCR, but a shorter duration of PCR positivity for asymptomatic patients. These findings suggest that asymptomatic patients may have more efficient clearance of virus, which may be relevant for management and screening.